Consumer Policy from Below Paradoxes, Perspectives, Problematizations - Hellmann, Kai-Uwe; Klein, Ansgar; Baule, Bernward (Springer Fachmedien Wiesbaden : Imprint: Springer, 2024)
X, 347 p. 13 illus., 7 illus. in color.